Encyclopedia of world cultures - Levinson, David 1947- (Boston, Massachusetts G.K. Hall, 1991)
A basic reference source to the cultures of the world. Provides descriptions of all the cultures of each region of the world or of a representative sample of cultures forregions where full coverage is impossible, as well as accurate descriptions of cultures of the past.
V. 1. North America / Timothy J. O'Leary, David Levinson, volume editors -- v. 2. Oceania / Terrence E. Hays, vol. ed. -- v. 3. South Asia / Paul Hockings, vol. ed. -- v. 4.Europe (central, western, and southeastern Europe) / LindaA. Bennett, vol. ed. -- v. 5. East and Southeast Asia / Paul Hockings, vol. ed. -- v. 6. Russia and Eurasia; China/ Paul Friedrich and Norma Diamond, vol. eds. -- v. 7. South America / Johannes Wilbert, vol. ed. -- v. 8. Middle America and the Caribbean / James W. Dow, vol. ed. -- v. 9. Africa and the Middle East / John Middleton and Amal Rassam, vol. eds. -- v. 10. Indexes.
Includes bibliographical references, filmographies, and indexes.
Also issued online.
Keywords: Ethnology -- Encyclopedias; Cultura -- Encyclopedias